2013
DOI: 10.1063/1.4858705
|View full text |Cite
|
Sign up to set email alerts
|

Growth study of branching coral Acropora formosa between natural reef habitats and in situ coral nurseries

Abstract: Abstract. Being a common reef building coral in Malaysian waters, growth of Acropora Formosa in natural reef habitat and coral nursery condition had been studied in aspects of extension growth, survival and proto-branch generation. The study sites took place at two separate islands with different environment conditions. In this study, A. formosa samples of natural reefs at Pangkor Island turbid waters recorded better growth in average extension rate (0.71 ±0.48 cm/month) and higher proto-branch generation rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…during past bleaching events (Marshall and Baird, 2000;Loya et al, 2001;McClanahan et al, 2002;Pratchett et al, 2013;Carroll et al, 2017). However, restoring with slower growing (and architecturally less complex) taxa is likely less beneficial for sites in need of fast recovery in terms of carbonate budgets (e.g., Tortolero-Langarica et al, 2019) and sustaining biodiversity (Lirman et al, 2010;Xin et al, 2016;Nithyanandan et al, 2018;Tiddy et al, 2021), but also where Acropora spp. were preferentially lost during recent bleaching of the GBR (Hoogenboom et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…during past bleaching events (Marshall and Baird, 2000;Loya et al, 2001;McClanahan et al, 2002;Pratchett et al, 2013;Carroll et al, 2017). However, restoring with slower growing (and architecturally less complex) taxa is likely less beneficial for sites in need of fast recovery in terms of carbonate budgets (e.g., Tortolero-Langarica et al, 2019) and sustaining biodiversity (Lirman et al, 2010;Xin et al, 2016;Nithyanandan et al, 2018;Tiddy et al, 2021), but also where Acropora spp. were preferentially lost during recent bleaching of the GBR (Hoogenboom et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Other reports on different reef restoration programs revealed that the average monthly growth rate of Acropora sp. ranged between 0.16cm and0.67cm (Oliver et al 1983;Clark & Edwards 1995;Putchim et al 2008;Anderson et al 2012;Xin et al 2016). The restoration efforts in Palk Bay resulted in high growth rates for A. muricata and A. hyacinthus, whereas the growth of Pocillopora damicornis was found least in numbers.…”
Section: Discussionmentioning
confidence: 99%
“…The process of fragment measurements was conducted with: a) identify the type of reef fragments sampled, namely reef fragments attached to each solid substrate (DC or DCA), then attached to the graft substrate and labeled with cable ties as markers [19], [20], b) Measure the branch length of each graft or fragment using a ruler. Fragments were measured from the base to the branch, the tip with ± 0.5 cm accuracy, and c) observing and counting live and dead number transplants, as well as calculating the increase of branches for each transplant on each substrate [21]. The process of measuring length growth can be seen in Figure 3.…”
Section: Data Collection Techniquementioning
confidence: 99%